THE POPULATION OF AQUATIC SWEED AND AEDES SPP. AND THE DISTRIBUTION PATTERN OF DENGUE FEVER DISEASE - Tien Aminatun; Tutiek Rahayu; Victoria Henuhili (Jurnal Penelitian Saintek, 2016)
The study was aimed at ﬁ nding out the abundance of aquatic weeds in Rowo Jombor, the population of Aedes spp live in aquatic weed area, and the distribution pattern of dengue fever disease related to the population of aquatic weed and Aedes spp. Field survey was conducted for two months to collect the weed population data, mosquito larvae density, and environmental sanitation condition of the villages around Rowo Jombor. The study used quantitative descriptive analysis to see the correlation among weed density, Aedes spp population. The interview was conducted to make its distribution pattern.The results show that: (1) the density of aquatic weeds in Rowo Jombor was dominated by Eichornia crassipes mainly on Location V near he outlet, while the Location III which was located in the center of the swamp, the aquatic weed was not found; (2) the larvae of Aedes spp population which lived in aquatic weed area was not found; and (3) the result could not prove the relationship between the pattern of dengue fever disease distribution and the aquatic weeds in Rowo Jombor as the habitat for mosquito larvae of Aedes spp.